CEA-regulated Oncolytic Virus Anticancer Therapy: A Promising Strategy for Rare Solid Tumors - Yang, Yuqi; Wang, Shuhang; Ma, Peiwen; Tang, Qiyu; Li, Yandong; Fang, Yuan; Zhu, Qi; Tao, Wei; Zha, Yan; Li, Ning (Current Cancer Drug Targets, 2022)
Background: Rare solid tumors have attracted much more attention due to the great unmet clinical need, limited treatment options, and poor prognosis. As the most thoroughly studied tumor marker, carcinoembryonic antigen (CEA) can not only overexpress in various common solid tumors but also in several rare solid tumors. Oncolytic virus therapy has achieved excellent anticancer effects in the past decades. Due to the specific high expression of CEA in certain tumor tissues but not in normal tissues, CEA has been applied to improve the tumor specificity of gene expression. Methods: The studies of CEA expression in rare solid tumors and CEA-regulated oncolytic virus therapy were reviewed. Results: We showed the types of rare solid tumors with the overexpression of CEA. Elevated serum CEA levels can indicate the diagnosis, response of surgery or system therapy, distal metastasis, recurrence, and survival. Due to high tumor specificity, CEA-regulated OA therapy has demonstrated a surprising antitumor effect for common CEA-positive tumors in preclinical trials. Conclusion: These data suggested that CEA could be a diagnostic and prognostic biomarker for several rare solid tumors. We proposed the hypothesis that CEA-regulated oncolytic virus therapy could be a promising therapeutic strategy for CEA-positive rare solid tumors.
Keywords: rare